Analysis of pastoral and farmers land conflict in Tanzania: A case study of Arumeru distict, - Helen, James (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management in partial fulfillment for the requirements of the award of degree of Master of Science of Human Resource Management o f Mzumbe University.